Ithaca forever : Penelope speaks, a novel - Malerba, Luigi (University of California Press, 2019)
After twenty years, Odysseus finally returns to Ithaca, but instead of receiving the homecoming he had hoped for finds himself caught in an intense battle of wills with his faithful and long-suffering wife Penelope. When Penelope recognizes him under the guise of a beggar, she becomes furious with him for not trusting her enough to include her in his plans for ridding the palace of the Suitors. As a result, she plays her own game of fictions to make him suffer for this lack of faith, inspiring jealousy, self-doubt, and misgivings in her husband, the legendary Homeric hero. In this captivati.